Repulsive Wnt Signaling Inhibits Axon Regeneration after CNS Injury - Liu, Yaobo (Society for Neuroscience, 2008)
Failure of axon regeneration in the mammalian CNS is attributable in part to the presence of various inhibitory molecules, including myelin-associated proteins and proteoglycans enriched in glial scars. Here, we evaluate whether axon guidance molecules also regulate regenerative growth after injury in adulthood. Wnts are a large family of axon guidance molecules that can attract ascending axons and repel descending axons along the length of the developing spinal cord. Their expression (all 19 Wnts) is not detectable in normal adult spinal cord by in situ hybridization. However, three of them are clearly reinduced after spinal cord injury. Wnt1 and Wnt5a, encoding potent repellents of the descending corticospinal tract (CST) axons, were robustly and acutely induced broadly in the spinal cord gray matter after unilateral hemisection. Ryk, the conserved repulsive Wnt receptor, was also induced in the lesion area, and Ryk immunoreactivity was found on the lesioned CST axons. Wnt4, which attracts ascending sensory axons in development, was acutely induced in areas closer to the lesion than Wnt1 and Wnt5a. Injection of function-blocking Ryk antibodies into the dorsal bilateral hemisectioned spinal cord either prevented the retraction of CST axons or promoted their regrowth but clearly enhanced the sprouting of CST collateral branches around and beyond the injury site. Therefore, repulsive Wnt signaling may be a cause of cortical spinal tract axon retraction and inhibits axon sprouting after injury.